Rethinking women's leadership in agrifood systems: Pathways to equality and resilience - Shijagurumayum, Meghajit Sharma; Morgan, Miranda Yeen; Elias, Marlene; Zaremba, Haley (2024)
This blog explores how reimagining women's leadership in agrifood systems can create new pathways to equality and resilience, fostering lasting change across sectors. Women are key actors in agrifood systems, participating on and off farm at different scales and across the public sector, private sector and civil society. However, there is a “dramatic imbalance” between women’s enormous and essential contributions to agrifood systems and their leadership and decision-making power. This global pattern holds true in India, where women often have less decision-making power than their male counterparts. Multiple forms of discrimination (for example, related to caste, ethnicity, disability and age) often overlap or intersect with gender inequalities, increasing the challenges for certain groups of women to claim their rights to participation and representation.